Carbon-catalyzed oxygen-mediated dehydrogenation of formaldehyde in alkaline solution for efficient hydrogen production - Lu, Nan (2022)
We report an efficient process to dehydrogenate formaldehyde in alkaline solution, catalyzed by carbon nanotubes (CNTs) via a unique reaction mechanism involving molecular O2. The superior catalytic performance of carbon nanotubes (CNTs) compared to the other carbon-based catalysts is attributed to their sp2-carbon-rich surface, hydrophilicity and abundant surface defects, which are the most plausible active sites. Peroxide species originating from the activation of adsorbed molecular oxygen on the CNTs is found to be a key to C–H activation, leading to efficient hydrogen production. The cost-effective carbon-based dehydrogenation catalysts offer new opportunities to the development of novel liquid organic hydrogen carrier technologies.